Assessment of animal diseases caused by bacteria resistant to antimicrobials: Swine - EFSA Panel on Animal Health and Welfare (AHAW); Søren Saxmose Nielsen; Dominique Joseph Bicout; Paolo Calistri; Elisabetta Canali; Julian Ashley Drewe; Bruno Garin‐Bastuji; Jose Luis Gonzales Rojas; Christian Gortazar Schmidt; Mette Herskin; Virginie Michel; Miguel Angel Miranda Chueca; et al. (EFSA Journal, 2021)
Abstract In this opinion, the antimicrobial‐resistant bacteria responsible for transmissible diseases that constitute a threat to the health of pigs have been assessed. The assessment has been performed following a methodology based on information collected by an extensive literature review and expert judgement. Details of the methodology used for this assessment are explained in a separate opinion. A global state of play of antimicrobial resistant Escherichia coli, Streptococcus suis, Actinobacillus pleuropneumoniae, Pasteurella multocida, Glaeserella parasuis, Bordetella bronchiseptica, Staphylococcus aureus, Staphylococcus hyicus, Brachyspira hyodysenteriae, Trueperella pyogenes, Erysipelothrix rhusiopathiae, Streptococcus dysgalactiae, Mycoplasma hyosynoviae, Mycoplasma hyorhinis, Mycoplasma hyopneumoniae and Brachyspira pilosicoli has been provided. Among those bacteria, EFSA identified E. coli and B. hyodysenteriae with > 66% certainty as being the most relevant antimicrobial resistant bacteria in the EU based on the available evidence. The animal health impact of these most relevant bacteria, as well as their eligibility for being listed and categorised within the animal health law framework will be assessed in separate scientific opinions.